Al-Ghazālī’s approach in refuting anthropomorphism - Nurhanisah Senin,; Khadijah Mohd Khambali @ Hambali,; Wan Adli Wan Ramli,; Mustafa Kamal Amat Misra, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Anthropomorphism stands at the heart of many theological discourses and is among the most discussed issues by Muslim scholars. Anthropomorphic descriptions of God are mentioned in several Quranic verses and hadith for instance, God’s hand, God’s laughter, God’s heavenly throne, God’s hand and fingers and others. More often than not, anthropomorphic verses were interpreted in a different manner according to a scholar’s theological affinity. Thus, this paper aims to examine al-Ghazālī’s method in dealing with anthropomorphic verses. Imam al-Ghazālī was among the Asha‘irah scholars who wrote extensively on theological and philosophical issues. By adopting document analysis method, this study explores al-Ghazālī’s methods by analyzing his writings mainly in Iḥyā’ ‘Ulūm al-Dīn and Fayṣal al-Tafriqah baina al-Islām wa al-Zindiqah, Iljām al-Awām ‘an Ilm al-Kalām apart from his other treatises such as al-Iqtiṣād fī al-‘Itiqād and Qānūn al-Ta’wīl. It can be found that al-Ghazālī strongly affirms God’s incorporeality by renouncing God’s essence from any bodily figures, space, accidents and directions. Apart from that, al-Ghazālī offered two different approaches in understanding anthropomorphic verses for the learned and laymen. For the learned, al-Ghazālī allowed strict allegorical interpretation with its rules. As for laymen, al-Ghazālī suggested seven steps in understanding antrhopomophic verses in ensuring the sanctity of God’s Essence from any figurative literal interpretation. In sum, this study demonstrates al-Ghazālī’s holistic approach in refuting anthropomorphism that includes the learned and laymen and ensuring one’s creed is preserved from any figurative understanding of God.